Uptake of evidence-based statin therapy among atrial fibrillation patients in China: A report from the CAFR (Chinese Atrial Fibrillation Registry) Study. (1st October 2016) - Xia, Shi-jun; Du, Xin; Li, Chao; Wu, Jia-hui; Tang, Ri-bo; Chang, San-shuai; Guo, Xue-yuan; Yu, Rong-hui; Long, De-yong; Bai, Rong; Liu, Nian; Sang, Cai-hua; et al.
Abstract: Background: Atrial fibrillation (AF) is associated with increased incidence of cardiovascular disease, and hence, statin therapy is indicated in majority of AF patients. Methods and results: We analyzed data from the Chinese Atrial Fibrillation Registry (CAFR) involving 11, 496 AF patients from 2011 to 2014. Practice patterns of statin therapy and factors associated with statin underuse were analyzed. Based on the 2013 ACC/AHA cholesterol management guidelines, statins should be recommended for 67.4% (7720/11, 461) of AF participants in CAFR, but only 43.4% (3352/7720) with appropriate indications were taking statins. Statin underuse in AF patients was independently associated with male sex, tertiary hospital treatment, outpatient attendance, and absence of 'high risk' cardiovascular risk factors (overweight, diabetes, coronary heart disease, stroke/transient ischemic attack/peripheral embolism and hypertension). Conclusions: A high proportion of Chinese AF patients had indications for statin therapy. Evidence-based statin prescribing was suboptimal in this population. Greater efforts should be made to improve a holistic approach to cardiovascular risk management in the Chinese AF population.